2001
DOI: 10.1063/1.1379579
|View full text |Cite
|
Sign up to set email alerts
|

The electronic structure and properties of group 8 oxides MO4, where M=Ru, Os, and Element 108, Hs

Abstract: Fully relativistic density functional calculations have been performed for group 8 tetroxides MO4, where M=Ru, Os, and element 108, Hs. The electronic structure analysis has shown HsO4 to be very similar to OsO4, with the covalence and stability increasing from OsO4 to HsO4. Using models of atom-slab interactions, adsorption enthalpies of RuO4 and HsO4 on the quartz surface have been calculated using some models of physisorption. The volatility of the single species was shown to have the following trend, RuO4&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 44 publications
5
54
0
1
Order By: Relevance
“…The results that best reproduce the experimental data suggest an adsorption enthalpy of −46 ± 2 kJ/mol for HsO 4 and −39 ± 1 kJ/mol for OsO 4 on the silicon nitride surface of the detectors. The significantly lower volatility of HsO 4 as compared to that of OsO 4 has been a surprize as a similar or slightly higher volatility for HsO 4 had been predicted [139,140]. The apparent discrepancy between experiment and theory has triggered new theoretical efforts by Pershina et al [146]; in this work, fully relativistic four-component density functional theory calculations were performed on MO 4 (M = Ru, Os and Hs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results that best reproduce the experimental data suggest an adsorption enthalpy of −46 ± 2 kJ/mol for HsO 4 and −39 ± 1 kJ/mol for OsO 4 on the silicon nitride surface of the detectors. The significantly lower volatility of HsO 4 as compared to that of OsO 4 has been a surprize as a similar or slightly higher volatility for HsO 4 had been predicted [139,140]. The apparent discrepancy between experiment and theory has triggered new theoretical efforts by Pershina et al [146]; in this work, fully relativistic four-component density functional theory calculations were performed on MO 4 (M = Ru, Os and Hs).…”
Section: Resultsmentioning
confidence: 99%
“…As the presumably very volatile tetroxide of hassium is an attractive object for a chemical characterization, fully relativistic density functional calculations of the electronic structure of the group-8 tetroxides MO 4 (M = Ru, Os, and Hs) have been performed by Pershina et al [139]. They found that the covalence and stability of the tetroxides increase from OsO 4 to HsO 4 .…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…The calculations have shown the compounds of the heaviest elements to be homologs of the lighter congeners in the chemical groups and bonding to be defined by the valence (n − 1)d AOs. An important finding is an increase in the stability of the maximum oxidation state and covalence in the groups, which is explained by increasing relativistic effects on the valence AOs [84,85,[96][97][98][99][100][101]. The RECP CCSD(T) calculations for the group-6 oxyhalides [96] have shown that the SO splitting of the 6d-AOs is a reason for a smaller D e of the 6d compounds with respect to the 5d ones.…”
Section: Atomic Propertiesmentioning
confidence: 99%
“…Prediction of ΔH ads of a heavy-element molecule on a surface is presently still a formidable task for first principle calculations. A way was, therefore, suggested in [98][99][100][101] to obtain ΔH ads indirectly with the use of physisorption models and accurate calculations of molecular properties. The models are based on the principle of molecule-slab interaction subdivided into usual types of long-range forces: dipole-dipole, dipole-induced dipole and van der Waals (dispersion) ones.…”
Section: Atomic Propertiesmentioning
confidence: 99%
“…A and B are the average dipole transition energies. In reference [55], the average dipole energies were replaced by the reciprocal of the first ionization potential. The physisorption energy can thus be written as…”
Section: Volatility and Interaction With Sio 2 And Aumentioning
confidence: 99%